Investigation of methods for estimating hand bone dimensions using X-ray hand anthropometric data. Issue 2 (3rd April 2017) - Kong, Yong-Ku; Freivalds, Andris; Kim, Dae-Min; Chang, Joonho
Abstract : This study examined two conversion methods, M1 and M2, to predict finger/phalange bone lengths based on finger/phalange surface lengths. Forty-one Korean college students (25 males and 16 females) were recruited and their finger/phalange surface lengths, bone lengths and grip strengths were measured using a vernier caliper, an X-ray generator and a double-handle force measurement system, respectively. M1 and M2 were defined as formulas able to estimate finger/phalange bone lengths based on one dimension (i.e., surface hand length) and four finger dimensions (surface finger lengths), respectively. As a result of conversion, the estimation errors by M1 presented mean 1.22 mm, which was smaller than those (1.29 mm) by M2. The bone lengths estimated by M1 (mean r  = 0.81) presented higher correlations with the measured bone lengths than those estimated by M2 (0.79). Thus, the M1 method was recommended in the present study, based on conversion simplicity and accuracy.